2005
DOI: 10.1038/sj.leu.2403760
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy of all-trans retinoic acid inducing signals for adult T-cell leukemia

Abstract: We previously reported that all-trans retinoic acid (ATRA) inhibits growth in human T-cell leukemia virus type 1 (HTLV-1)-positive T-cell lines and fresh cells from patients with adult Tcell leukemia. However, the mechanism of this inhibition is not clear. In the present study, we observed that NF-jB transcriptional activity as well as cell growth decreased significantly in HTLV-1-positive T-cell lines in the presence of ATRA. Furthermore, we observed that ATRA reduced HTLV-1 proviral DNA, HTLV-1 genes (gag, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Furthermore, HTLV-1 proviral DNA load was also significantly decreased by ATRA in HTLV-1-positive T-cell lines (all five HTLV-1-positive T-cell lines at 48 hours, and ATL-2, HUT102, MT-4 and ED40515 at 72 hours). These results suggested that ATRA might act as a RT inhibitor (Yamaguchi et al, 2005). Moreover, HTLV-1 tax mRNA load was significantly suppressed by ATRA (HUT102 and MT-2 at 48hours).…”
Section: Mechanism Of Atra Action For Atl Cellsmentioning
confidence: 57%
See 4 more Smart Citations
“…Furthermore, HTLV-1 proviral DNA load was also significantly decreased by ATRA in HTLV-1-positive T-cell lines (all five HTLV-1-positive T-cell lines at 48 hours, and ATL-2, HUT102, MT-4 and ED40515 at 72 hours). These results suggested that ATRA might act as a RT inhibitor (Yamaguchi et al, 2005). Moreover, HTLV-1 tax mRNA load was significantly suppressed by ATRA (HUT102 and MT-2 at 48hours).…”
Section: Mechanism Of Atra Action For Atl Cellsmentioning
confidence: 57%
“…HTLV-1 proviral DNA load was only decreased by VP-16 in MT-2. HTLV-1 proviral DNA load was significantly suppressed by AZT in the HTLV-1-positive T-cell lines (ATL-2 and MT-2 at 48 hours, and ATL-2, MT-2, MT-4 and ED40515 at 72 hours) (Yamaguchi et al, 2005). Furthermore, HTLV-1 proviral DNA load was also significantly decreased by ATRA in HTLV-1-positive T-cell lines (all five HTLV-1-positive T-cell lines at 48 hours, and ATL-2, HUT102, MT-4 and ED40515 at 72 hours).…”
Section: Mechanism Of Atra Action For Atl Cellsmentioning
confidence: 99%
See 3 more Smart Citations